FAKTOR-FAKTOR PENENTU SEBAGAI DETERMINAN ANAK STUNTING DI INDONESIA - Sheira Indah Anjani (Fakultas Ilmu Keperawatan Universitas Klabat, 2022)
The prevalence of stunting in Indonesia continues to decline by 27.67% based on the results of the 2019 Indonesian Toddler Nutritional Status Study (SSGBI) which also shows that the stunting rate in Indonesian toddlers is quite far from the 20% standard set by WHO. The purpose of compiling this study is to identify the determinants of stunting in children due to the high prevalence of stunting in Indonesia. The method used in this study is an observational study and a systematic literature review. Searches were made with keywords in PubMed, PubMed Central (PMC), and Web of Science published from 2012 to present. Then, obtained 86 results from PubMed, 1,624 from PMC, and 69 from Web of Science and selected 15 studies deemed relevant. Proximal factors such as household factors, breastfeeding practices and complementary feeding, as well as distal factors such as infection and social environment are the determinants of stunting in Indonesia.